METHODOLOGICAL ASPECTS OF STUDYING FINANCE - V. A. Tyurnin (Финансы: теория и практика)
The article addresses some aspects of finance, a sufficiently complicated economic category that is insufficiently developed in modern scientific literature. According to the author, the holistic view of the finance is closely related to the study of genetic and functional aspects of finance, their interdependence and interaction. The author made an attempt to look on the finance from the genetic point of view. The finance as an economic category is considered from different perspectives: as the object and subject of utilization (consumption), in terms of its nature, its role as a subject in social reproduction, as well as its functionality. As a synthetic economic category, the finance is connected with definite steps of the reproduction process at all levels of the economy, represents a complex of economic relations in terms of formation, distribution, re-distribution and use of centralized and decentralized funds as well as non-fund forms of accumulation in the process of establishment, distribution, re-distribution and use of the gross domestic product and the national income of the state.